Unprovoked hemothorax : an unusual presentation in Dengue Haemorrhagic Fever - Manappallil, Robin George (Asian Journal of Medical Sciences, 2016)
According to WHO, Dengue fever (DF) is the most rapidly spreading mosquito-borne viral disease in the world. Dengue Haemorrhagic fever (DHF) is a severe and more serious form of DF, characterised by fever, bleeding manifestations, plasma leakage and thrombocytopenia. This is a case of a 28 year old male, who presented with history of fever and myalgia and was diagnosed to have DF. He had developed acute onset dyspnoea and his chest X-Ray showed right sided pleural effusion. Pleurocentesis revealed haemorrhagic fluid in the absence of trauma.Unprovoked hemothorax as an initial presentation of DHF has rarely been reported. Asian Journal of Medical Sciences Vol.7(3) 2016 121-122